Developing Lecturers’ Research Performance Monitoring and Evaluation System: A Study from Politeknik Negeri Bandung - Carolina Magdalena Lasambouw; Ediana Sutjiredjeki; Neneng Nuryati (Soshum: Jurnal Sosial dan Humaniora, 2019)
Currently, research performance becomes one of the criterias to determine a university’s rank. This performance is highly dependent on the individual lecturer's research performance. Hence, continuous evaluation of individual lecturer's research performance becomes very important. Lecturer’s performance evaluation is generally done through Lecturer Performance Planning (LPP) and Lecturer Performance Achievement (LAP). However, LPP/LAP does not reflect the actual achievement and overall performance of inidividual lecturer. Thus, a monitoring and evaluation system on the research performance of individual lecturer is necessary to address the issue. The findings presented on this research paper were developed using mixed methods. The qualitative approach was done through observation and interview to gather information on individual research performance. A valid and reliable questionnaire was also developed based on the data obtained from 128 lecturers in Polban who were selected based on purposive random sampling. The collected data were tabulated and described descriptively. Accordingly, a Performance Monitoring Framework of Individual Researcher has also been developed. The final output of this research is an individual research performance mapping. This mapping will be useful for designing research policy to improve the capacity and quality of individual lecturer's performance, which in turn will contribute to improving research performance of related institution.